Oral surgery in patients under antithrombotic therapy. Narrative review. - Anggelo Carrizo; David Carrasco (Universidad de Concepción., 2015)
Population aging and the increasing rates of cardiovascular diseases have raised the number of patients receiving antithrombotic therapy in elective or emergency dental care, including surgical procedures. The aim of this article is to review the evidence and clinical guidelines for management of patients on antithrombotic therapy published in the past five years. The American Antithrombotic Therapy Guideline - 2012 - generally recommends not to suspend antiplatelet or anticoagulant treatment in dental procedures since they are considered to have low bleeding risk and easy resolution. In the dental field, there is ample published evidence regarding oral surgical procedure management, especially by maxillofacial surgeons, showing a low number of complications associated with extractions or other minor oral surgical procedures without suspending antithrombotic drugs and only taking some minimum safeguards, such as healing by first intention or the use of some local hemostatic agents. In general, patients under chronic antithrombotic therapy should keep their medication when undergoing low and medium complexity dental procedures, since complications are minor and easy to handle. Due to interactions between them, particular care should be taken with patients using more than one drug.